21.6k views
4 votes
Y+1/3y+1=9 B= Y= Check

Y+1/3y+1=9 B= Y= Check-example-1

1 Answer

6 votes

y + (1/3)y + 1 = 9

We can simplify the left side of the equation by combining the two terms with y:

(4/3)y + 1 = 9

Subtracting 1 from both sides:

(4/3)y = 8

Multiplying both sides by 3/4:

y = 6

So the value of y that satisfies the equation is y = 6.

To check our answer, we can substitute y = 6 into the original equation:

y + (1/3)y + 1 = 9

6 + (1/3)(6) + 1 = 9

6 + 2 + 1 = 9

9 = 9

The equation is true, so our solution y = 6 is correct.

User Robert Parker
by
7.6k points